Multi-locus phylogeny and taxonomic revision of Uperoleia toadlets (Anura: Myobatrachidae) from the western arid zone of Australia, with a description of a new species - Catullo, Renee A.; Doughty, Paul; Roberts, J. Dale; Keogh, J. Scott (Zootaxa, 2011)
We generated a multi-locus phylogeny to test monophyly and distributional limits in Australian toadlets of the genus Uperoleia from the western arid zone of Australia. The molecular data were used in combination with a detailed assessment of morphological variation and some data on call structure to complete a taxonomic revision of the species that occur in this region. Our work reveals the existence of not two but five species in the region. Uperoleia russelli is restricted to the Carnarvon and Gascoyne Regions south of the Pilbara. Uperoleia micromeles is distributed from the Tanami Desert through the Great Sandy Desert and along the northern edge of the Pilbara. Uperoleia talpa was previously believed to be a Fitzroyland region endemic but it is further distributed along Dampierland and into the Roebourne Plain. Uperoleia glandulosa is a larger species than previously described as well as a greater habitat generalist, inhabiting the rocky Pilbara region and the sandy region around Port Hedland. We also describe a new species, U. saxatilis sp. nov., endemic to the Pilbara craton.